Implementing Flipped Learning in Teaching Sociolinguistic Analysis - Ismatovna, Baybabayeva Shoiraxon; Nilufar, Usmanova (International Journal on Human-Computing Studies, 2023)
The article deals with the issues based on implementing flipped learning in teaching sociolinguistic analysis. The main attention is focused on the selection of the "flipped classroom" educational technology, which is referred to as blended learning models. The flipped classroom learning model consists of the following components: updated content, interactive methods, organizational forms, traditional and distance learning tools, and a set of self-developed tasks and exercises for the three stages of working with feature films (pre-viewing, viewing, post-viewing).